An aggregate-level macro model for the Indian economy - Naoyuki Yoshino; Rajendra Narayan Paramanik; K. U. Gopakumar; Farhad Taghizadeh-Hesary; Ma. Laarni Revilla; Kallidaikurichi Seetharam (Asian Development Bank Institute (ADBI), 2020)
This research piece is an empirical attempt to model the Indian economy at an aggregate level with annual data, ranging from 1980 to 2019. The major theoretical premise of the paper mimics the New Keynesian framework, which is based on the microeconomic foundations of Keynesian economics. The paper proposes a whole economic structure in the form of nine equations. Aggregate demand is modeled with the help of four equations, representing consumption, private investment, exports, and imports. Aggregate supply assumes the form of a simple neoclassical production function where labor, capital, and exogenous technical progress are considered as inputs. Further, inflation is assumed to follow a New Keynesian representation whereas the LM curve has its standard form with income and short-term rate of interest as its determinants. Subsequently, a linking equation, expressing long-run interest rates as a function of short-term interest rates and government investment, is proposed to unify monetary policy and fiscal policy to goods markets. Finally, tax is estimated as a function of per capita income. A structural equation model is employed for the empirical analysis and findings support the theoretical expectations. Consumption follows the absolute income hypothesis and private investment is governed by the accelerator principle. Further, the negative sign of nominal interest rates in the investment function confirms an inverse relation between the former and private capital formation. Exports are found to be influenced by world income, exchange rates, and government capital formation, and import demand is determined by domestic income, the difference between domestic and international inflation, and the lagged exchange rate. From the policy perspective, this paper suggests the suitability of fiscal and monetary policies for increasing growth in the Indian economy. However, the effectiveness of expansionary fiscal policy is observed to have a larger impact on growth than easy monetary policy. This inference is drawn mainly on the basis of a simulation exercise for the proposed structural equation model.
Keywords: C36; E1; E27; 330; New Keynesian model; structural equation model; Indian economy